Landslides 2022
DOI: 10.5772/intechopen.99864
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Landslide Susceptibility of Şavşat District of Artvin Province (Turkey) Using Machine Learning Techniques

Abstract: The aim of this study is to produce landslide susceptibility maps of Şavşat district of Artvin Province using machine learning (ML) models and to compare the predictive performances of the models used. Tree-based ensemble learning models, including random forest (RF), gradient boosting machines (GBM), and extreme gradient boosting (XGBoost), were used in the study. A landslide inventory map consisting of 85 landslide polygons was used in the study. The inventory map comprises 32,777 landslide pixels at 30 m re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…These factors are related to topography (T_E, T_F_acc, T_FLAT, T_NW, T_TPI, T_S, T_TWI, T_VRM, T_W), seismicity (S_Epic), geolithology (G_TA, G_SSC, G_CM, G_C, G_DDB, G_LG, G_SC, G_SSM, G_CCL, G_ML), land cover (LU_urb, LU_grs, LU_for, LU_nat), morphology (D_riv, D_road), and climate (C_p_max). It is well known [48][49][50][51] that the slope length and steepness factor (T_Ls) is one of the main landslide predictors, being a parameter used to characterize the effects of topography and hydrology on soil loss [52,53]. In our study, the T_Ls showed the highest coefficient in predicting the totality of recorded events and one of the most predicting variables for the other landslide types, evidencing its influence in the evolution of landslide types.…”
Section: Correlation Analysissupporting
confidence: 54%
See 1 more Smart Citation
“…These factors are related to topography (T_E, T_F_acc, T_FLAT, T_NW, T_TPI, T_S, T_TWI, T_VRM, T_W), seismicity (S_Epic), geolithology (G_TA, G_SSC, G_CM, G_C, G_DDB, G_LG, G_SC, G_SSM, G_CCL, G_ML), land cover (LU_urb, LU_grs, LU_for, LU_nat), morphology (D_riv, D_road), and climate (C_p_max). It is well known [48][49][50][51] that the slope length and steepness factor (T_Ls) is one of the main landslide predictors, being a parameter used to characterize the effects of topography and hydrology on soil loss [52,53]. In our study, the T_Ls showed the highest coefficient in predicting the totality of recorded events and one of the most predicting variables for the other landslide types, evidencing its influence in the evolution of landslide types.…”
Section: Correlation Analysissupporting
confidence: 54%
“…Concave shape also affects the development of rotational/translational mass movement, reflecting the importance of the hydrological regime in slope stability. In these areas, a convergence of surface and subsurface water streams saturates rapidly the soil, which becomes more prone to movements [51].…”
Section: Correlation Analysismentioning
confidence: 99%
“…While XGBoost shares some parameters with other tree-based models, it involves additional hyperparameters to control the overfitting concern, enhance precision, and mitigate forecasting variance [82]. This study develops the landslide susceptibility model using the "XGBoost" package in R 4.0.2 software, which provides powerful capabilities for classification tasks [83]. In this research, three general parameters were chosen for us to alter in the XGBoost algorithm for LSM application: nrounds (the maximum number of boosting repetitions), subsample (the subsample ratio of the training instance), and colsample_bytree (the subsample ratio of columns while constructing each tree).…”
Section: Rfmentioning
confidence: 99%
“…Nonlinear models better identify the nonlinear relationship between predictor variables and CW-SOC content, solve the problem of spatial autocorrelation [14,21], and have good generalization performance. This is especially the case for machine learning methods based on decision tree models, such as random forest (RF), gradient boosting machine (GBM), and extreme gradient boosting (XGBoost) [22]. They show good performance in predicting SOC content, especially when dealing with complex and high-dimensional data.…”
Section: Introductionmentioning
confidence: 99%